THE INFLUENCE OF THE PROCESS OF STARCH MODIFICATION WITH LACTIC ACID ON THE PROPERTIES OF FILMS - KUCHYNSKA, DARIA; ISHCHENKO, OLENA; YASHCHUK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The increasing demand for effective and sustainable wound care solutions has driven the development of innovative materials. This study focuses on the creation of biodegradable polymeric films based on starch modified with lactic acid and polyvinyl alcohol. These films are designed to serve as advanced wound dressings with the potential for sustained drug delivery.Starch was modified through a controlled acid hydrolysis process using lactic acid solutions of varying concentrations (0.5 and 1.0 mol/L) at a temperature of 40°C for 2 hours. The degree of modification was carefully controlled to achieve desired properties. Subsequently, the modified starch was blended with polyvinyl alcohol in specific ratios (25:75, 50:50, and 75:25) to form a film-forming solution. Films were produced using a casting technique, followed by drying to remove the solvent.The physicomechanical properties of the films were significantly influenced by the modification conditions. Increasing the concentration of lactic acid resulted in enhanced film strength, likely due to increased crosslinking between polymer chains. Optimal mechanical properties were achieved for films composed of 25% modified starch and 75% polyvinyl alcohol, with a tensile strength of 7.31 ± 0.2 MPa and an elongation at break of 50.16 ± 2.5%.The water vapor sorption capacity of the films was also investigated. This controlled moisture management can promote optimal wound healing.The developed polymeric films demonstrate promising potential for use in advanced wound dressings. Their biocompatibility and tunable properties make them suitable for various wound care applications. Further research will focus on incorporating antimicrobial agents and bioactive molecules into the films to enhance their therapeutic efficacy. Additionally, studies on the release kinetics of drugs from these films will be conducted to optimize their sustained drug delivery capabilities.
Keywords: modified starch; polyvinyl alcohol; lactic acid; wound dressings; sustained drug release; moisture sorption; tensile strength; biocompatibility